Glass fibre content of PP plates and their properties: part II: tensile mechanical properties - Neves, N. M. (2002)
Short fibre reinforced polypropylene compounds have been used to produce composites taking advantage of its interesting properties and competitive raw material prices. For the same reason the short glass fibres are the most used reinforcement in injection moulded thermoplastic composites. In injection moulding, varying patterns of fibre orientation are obtained through the thickness direction and along the flow path. Moulding parameters such as injection flow rate or melt-temperature do affect the fibre orientation distributions in mouldings. It has been observed that the type of flow, being dominated by shear stresses (e.g. linear flow) or by extensional stresses (e.g. radial flow) affects the fibre orientation field. Other parameters may have an effect over the fibre orientation such as the fibre length distribution. During processing some degree of fibre breakage in unavoidable. The fibre contents, its length and orientation distributions cause anisotropy on mechanical properties. Efficient reinforcements are obtained in the direction of major orientation of the fibres and when longer fibres are used. In this work the effect of various fibre contents, by volume (0, 10, 20 and 25%) over the anisotropy of mechanical properties of injection moulded rectangular plates is explored. Specimens cut along and across the flow directions are subjected to tensile tests enabling to discuss the anisotropy of tensile mechanical properties.